Hospital based study on causes of low vision and patient preference for different types of low vision devices - KC, BK; Thapa, HB; Gurung, S; Sherchan, A; Karthikeyan, AS; Kandel, RP (Journal of Institute of Medicine Nepal, 2007)
Background: In accordance with the objectives envisaged by the Vision 2020 WHO global initiative, this study was designed to reveal the causes of low vision (LV), patient preference for and acceptance of specific types of low vision devices. The study was performed between January, 2006 and December, 2006 at the Low Vision Clinic in Lumbini Eye Institute (LEI). Materials and Methods: A descriptive clinical study of patients with low vision was performed. All patients were examined by an Ophthalmologist and an Optometrist. Un-corrected visual acuity (VA), best-corrected visual acuity (BCVA), visual loss based on anatomical sites, low vision assessment was performed and patient preference for a specific low vision device was observed and documented. Standard National Low Vision Assessment Form was used. Results: A total of 166 new Nepali patients were included in the study out of whom 70% were male. Of these patients, lens related causes like aphakia, pseudophakia was the main cause of low vision in 35.55% patients, followed by refractive errors / amblyopia accounted for 19.23%, retinitis pigmentosa for 10.84%, whole globe abnormalities 10.25%, corneal pathology accounted for 7.24%, retinal disease (different types of maculopathies, retinal scars, retinal hemorrhages, vein occlusion, etc.) in 6.64%, and other causes (albinism, nystagmus, different syndromes, etc.) in 10.25%. In low vision assessment, 6.02 % not needed any device (sufficient near vision enough to conduct his or her near task without any type of devices / glasses) as per the guidelines set up by National Low Vision Programme), distance glasses gave enough improvement for 19.27%, spectacle magnifier was preferred by 51.80%, other magnifiers (hand/stand/dome) was preferred by 12.65%, and monocular handheld telescope was preferred by 20.48% for distance. The above includes certain patients requiring assistance with both near and distance vision who opted for multiple LV devices (i.e., for near and distance vision separately) instead of LV devices with multiple functionality. In non-optical Low-vision devices, 25 % preferred reading lamp, 10 % preferred reading stand, 12% preferred black felt tip pen, 6 % preferred sunglasses, 7 % preferred peaked cap, 4 % preferred typoscope, and 3 % preferred LV note book. Conclusion: Lens related causes and refractive errors/amblyopia seem to be two of the most important causes of low vision and should not be overlooked. In addition, low vision devices with a usage similar to that of spectacles were preferred by patients for near and telescope for distance. Keywords: Visual impairment, low vision devices, patient preference, causes of low vision. The full text of this paper is available at Journal of Institute of Medicine website